Microbiological evaluation of the potencies of brands of four parenteral antibiotic preparations used in the treatment of urinary tract infections (2015)
Urinary tract infection (UTI) is a common disease and sometimes life threatening if not properly treated. In Nigeria, aside adulteration and counterfeiting of antibiotics, potency of antibiotics can also be altered by factors like production errors and storage condition at the Pharmacy stores. This study investigated the potencies of selected brands of four common parenteral antibiotic preparations, in Nigerian drug markets against uropathogens isolated from patients with recurrent UTI. Ten selected clinical bacterial isolates from patients with recurrent UTI were collected from the Microbiology unit of the University College Hospital, Ibadan and authenticated by standard bacteriological methods. The isolates were subjected to susceptibility test against eight standard antibiotics by disc diffusion method. The selected brands of the four parenteral antibiotic preparations used in this study includes: Ciprofloxacin (Emason® and Uniflox®); Ceftriaxone (Rocephin® and Cefin®); Aminoglycoside (Pe-genta® and Philo-genta®) and Aminopenicillin/inhibitor (Augmentin® and Amoxiclav®). Efficacies of the parenteral antibiotic preparations against the isolates were determined by Minimum Inhibitory Concentrations (MICs) using broth-dilution method. L'EVALUATION MICROBIOLOGIQUE DES PUISSANCES DES MARQUES DE QUATRES PREPARATIONS ANTIBIOTIQUES PARENTERALES UTILISEES DANS LE TRAITEMENT DE L'INFECTION DES VOIES URINAIRES. *ALABI O.S et AJOSE A. O